A recurrent, ischaemic ileocolonic anastomosis ulcer refractory to surgery treated with hyperbaric oxygen - Pateria, Puraskar (Diving Hyperb Med, 2018)
A 54-year-old male had undergone right hemicolectomy and ileo-colonic anastomosis for carcinoma-in-situ found at colonoscopy. Eighteen months later, he presented with a lower gastrointestinal bleed from an anastomotic ulcer, treated with resection of the anastomotic site and ileo-sigmoid anastomosis. In the ensuing 12 months, he had three episodes of haematochezia. Colonoscopy revealed a 12 mm anastomotic ulcer necessitating a further colonic resection and re-anastomosis. Two-years later, he presented with iron deficiency anaemia. He preferred expectant management and received ten iron-infusions over the subsequent four years. Thereafter, he developed painless haematochezia. Colonoscopy showed a 15 mm linear ulcer with mild ooze at the anastomosis. Histology was consistent with an ischaemic ulcer; there was no evidence of recurrence of carcinoma-in-situ. The ulcer remained refractory to endoscopic and medical treatment, as seen at three follow-up colonoscopies. Hyperbaric oxygen treatment (HBOT) was offered and he received 30 sessions over six weeks. Colonoscopy at HBOT completion revealed healing of the ulcer. The patient had no further overt bleeding and serum ferritin has continued to rise spontaneously over 12 months follow-up.